Research knowledge transfer to improve the care and support of adolescents with sickle cell disease in Ghana - Brenda A. Poku; Alison Pilnick (Wiley, 2022)
Abstract Introduction Effective transfer of research findings to key knowledge users, particularly in low‐ and middle‐income countries, is not always achieved, despite being a shared priority among researchers, funders, healthcare and community stakeholders and decision‐makers. A constructivist grounded theory study conducted in 2015-2019 in Ghana that explored sickle cell‐related fatigue in adolescence resulted in numerous implications for practice and policy. Peer‐reviewed funding was obtained to support disseminating these findings to relevant stakeholders. Methods Key steps in implementing this study dissemination project included: (1) identifying and attracting target stakeholders from healthcare and community organizations; (2) tailoring tools for communication of research findings for the stakeholder groups and (3) designing interactive workshops to facilitate knowledge sharing and uptake. Finding Despite the COVID‐19 pandemic, 50 healthcare and community stakeholders participated in the dissemination workshops. The dissemination activities contributed new layers of understanding to the original research findings through discussions. Through the workshops, participants identified culturally valuable and actionable recommendations that they could take forward to improve care and support for young people with sickle cell disease in Ghana. A follow‐up 6 months post the workshops indicated some positive knowledge usage and benefits. Conclusion This dissemination project provided a unique opportunity for researchers and stakeholders to share in the interpretation of research findings and to strategically plan recommendations to improve SCD‐focused care and support for young people in Ghana. Further research dissemination should continue to be grounded in locally generated knowledge, include systematic, long‐term evaluation of dissemination outcomes and be adequately financed. Patient and Public Contribution Public involvement in this study was critical to the research dissemination project. The Sickle Cell Association of Ghana (Kumasi chapter) actively supported the project's development, organization and facilitation. Parent members of the Association, the Association's executive members and volunteers, and the health professionals involved in sickle cell care at the Komfo Anokye Teaching Hospital participated in the project workshops. They contributed to the knowledge transfer and uptake.